The broken eye ebook - Weeks, Brent (Lightbringer, 2014)
As the old gods awaken and satrapies splinter, the Chromeria races to find the only man who can still end a civil war before it engulfs the known world in the third novel of the NYT bestselling Lightbringer series by Brent Week. As the old gods awaken and satrapies splinter, the Chromeria races to find the only man who can still end a civil war before it engulfs the known world. But Gavin Guile has been captured by an old enemy and enslaved on a pirate galley. Worse still, Gavin has lost more than his powers as Prism — he can't use magic at all. Without the protection of his father, Kip Guile will face a master of shadows as his grandfather moves to choose a new Prism and put himself in power. With Teia and Karris, Kip will have to use all his wits to survive a secret war between noble houses, religious factions, rebels, and an ascendant order of hidden assassins called The Broken Eye. Read the third book in Brent Weeks's blockbuster epic fantasy series that had Peter V. Brett saying, "Brent Weeks is so good, it's starting to tick me off!" .